PENGARUH Pengaruh Marketing Mix Strategies and Their Influence on Consumer Loyalty: A Quantitative Approach - Rahmawati, Arisky Af Idatul; Hapsari, Radhita Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the influence of the marketing mix, consisting of promotion, price, product, and place, on consumer loyalty at Anik Frozen Food Purwodadi. Design/Methodology/Approach – This study employs a quantitative research approach. The population consists of Anik Frozen Food’s Instagram followers, with 100 respondents selected as the sample using a non-probability sampling technique. Data were collected through online questionnaires and analyzed using SPSS version 25. Multiple linear regression analysis was applied to examine the relationship between marketing mix variables and consumer loyalty. The research instruments were tested using validity and reliability tests, while classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to ensure the validity of the regression model. Hypothesis testing was performed using the F-test and t-test, supported by the coefficient of determination (R²). Findings – The analysis reveals the extent to which promotion, price, product, and place influence consumer loyalty at Anik Frozen Food Purwodadi. The findings provide insights into the effectiveness of marketing mix strategies in strengthening customer relationships and improving competitiveness in the frozen food retail sector. Originality/Value This research is original in utilizing social media followers as the study population to evaluate marketing mix effectiveness. The findings provide practical value by guiding retailers in prioritizing promotional, pricing, product, and distribution strategies to enhance customer retention.